2005
DOI: 10.1002/kin.20110
|View full text |Cite
|
Sign up to set email alerts
|

Carbothermal synthesis of titanium nitride (TiN): Kinetics and mechanism

Abstract: Constant rate thermal analysis (CRTA) has been used for studying the kinetics of the carbothermal reduction of anatase in nitrogen. It is noteworthy to point out the ability of CRTA method for discriminating the kinetic law of solid-state reactions with considerably higher precision than conventional (TG, DTA, isothermal etc.) methods. The precise control of the reaction rate implies either direct or indirect control of both the partial pressure of CO generated in the reaction and the heat evolution rate, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…In fact, in carbothermal reduction of titania without nitrogen, conversion of Ti 2 O 3 to TiO x C y was the slowest stage, whereas in the presence of nitrogen, fast conversion of Ti 2 O 3 to TiO x C y N z left conversion of Ti 3 O 5 to Ti 2 O 3 as the slowest. Formation of titanium oxycarbonitride in carbothermal reduction in the presence of nitrogen, observed in this work, was in disagreement with the conclusion by Jha and Yoon 4 that titanium carbonitride was the resulting phase formed in the carbothermal reduction/nitridation of titania at 1200°C-1500°C, and with White et al 14 and Ortega et al 15 who reported formation of TiN. The conclusion that titanium nitride or carbonitride formed was based on the XRD analysis; however, titanium carbonitride, nitride, and oxycarbonitride have the same crystal structure (cubic) with very close crystal parameters.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In fact, in carbothermal reduction of titania without nitrogen, conversion of Ti 2 O 3 to TiO x C y was the slowest stage, whereas in the presence of nitrogen, fast conversion of Ti 2 O 3 to TiO x C y N z left conversion of Ti 3 O 5 to Ti 2 O 3 as the slowest. Formation of titanium oxycarbonitride in carbothermal reduction in the presence of nitrogen, observed in this work, was in disagreement with the conclusion by Jha and Yoon 4 that titanium carbonitride was the resulting phase formed in the carbothermal reduction/nitridation of titania at 1200°C-1500°C, and with White et al 14 and Ortega et al 15 who reported formation of TiN. The conclusion that titanium nitride or carbonitride formed was based on the XRD analysis; however, titanium carbonitride, nitride, and oxycarbonitride have the same crystal structure (cubic) with very close crystal parameters.…”
Section: Discussioncontrasting
confidence: 84%
“…Formation of titanium oxycarbonitride in carbothermal reduction in the presence of nitrogen, observed in this work, was in disagreement with the conclusion by Jha and Yoon that titanium carbonitride was the resulting phase formed in the carbothermal reduction/nitridation of titania at 1200°C–1500°C, and with White et al . and Ortega et al . who reported formation of TiN.…”
Section: Discussionmentioning
confidence: 99%
“…20 High surface area TiN is used as catalysts for the C-C coupling of alcohols and ketones, 21 the reduction of alkynes to alkenes, 22 and as electrode materials for electrochemical energy storage and conversion devices. [23][24][25] The conventional methods such as nitridation of Ti metal 26 and carbothermal reduction followed by nitridation 27 produce microcrystalline particles. TiN nanoparticles have been synthesized by laser ablation, 28 ammonolysis of TiO 2 or TiCl 4 L (L = donor ligand), 29 and aerosol techniques, reported to produce nanopowders with spherical morphology.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reaction temperature could be decreased with the decrease of concentration of CO in this system . It can be deduced from the gas analysis mentioned above that the composition of CO gas in this system is less than 5% with a maximum of 6942 ppm; while N 2 , as a main carrier gas, could account for at least 50% of the whole gas system.…”
Section: Results and Discussionmentioning
confidence: 99%